Writing scientific thesis/ dissertation in biology field: Discussion writing problems - Salman, Huda Dawood (Iraqi Journal of Cancer and Medical Genetics, 2017)
Theses or dissertations contain many chapters; the most vital and important one is the discussion chapter. Most other chapters were previously investigated for writing problems and the results revealed so many mistakes in the writing process. However, the discussion chapter still hasn’t been studies in these theses or dissertations. Therefore, the context of discussion writing was studied and analysed in 124 theses and dissertations of Iraqi postgraduate students in the field of biology to assess the major problems and mistakes facing the discussion text writing. At the same time an interview was carried out with 114 students from the same field to obtain soild idea about the awarness of those students in the discussion writing style. The study involved many factors and criteria used internationally to analyse the situation of discussion writing. The results revealed that most students have little knowledge or no idea about discussion writing process. The writing process showed many mistakes contextually, structurally and scientifically. It was well realized that the students, before they wrote their theses or dissertations, hadn’t previously possessed any information about the writing discussion text and they wrote them as previous student did regardless of they were correct or not. This study concluded that postgraduate students wrote their theses or dissertation in unsystamatic random style indepent of proper writing rules or criteria indicating their ignorance to the right style of writing proper discussion text. This invites the Universities to evaluate that and establish a plan to make the students in a level that they have sufficient awareness of scientific writing.